(untitled) (Al-Farooq Journal of Sciences, 2026)
The economic activity and pattern of renewal during the caliphate of Caliph Uthman ibn Affan (may Allah be pleased with him) witnessed remarkable economic prosperity as a result of the expansion of the Islamic state and the increasing number of conquests. This led to a significant growth in the revenues of the public treasury (Bayt al-Mal), as well as the expansion of trade, agriculture, and craft industries. Uthman also paid special attention to securing trade routes, surveying lands, and encouraging production. The importance of this study lies in highlighting Uthman’s role in improving the economic conditions of Muslims through the flourishing of trade, agriculture, and handicrafts, while supporting the Islamic conquests by providing the necessary financial resources, thereby strengthening the position, unity, and stability of the Islamic state. The study addresses the following research problem: How did Caliph Uthman ibn Affan transform the economic system during his reign from a rent-based economy into an investment-oriented economy founded on the renewal of economic institutions? Furthermore, what was the impact of this transformation on the development of the Islamic state? The study adopts the descriptive historical method by tracing historical events and developments related to economic activity and patterns of renewal during the caliphate of Uthman ibn Affan, then describing and analyzing them to identify the major features of economic prosperity and the reforms implemented during his reign, as well as their contribution to strengthening the Islamic state and ensuring its stability.